Guardian or Saboteur? The State and the Right to Choice in Marriage - Chowdhry, Prem (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
The failure of the judicial system to ensure effective protection of the right to choice in marriage, especially in the face of modern, equitable law, and /or collusion of state agencies in sabotaging this right, is assuming alarming and dangerous proportions. This paper argues that, although the introduction of modern concepts like adulthood and the sanctity of individual rights has legalised the individual settlement of marriage between two consenting heterosexual adults, the emphasis is missing on a dynamic liberal and progressive implementation of legal rights. Instead, their infringement is aided by acceptance of customary norms that empower the family or community to take marriage decisions on behalf of individual members. This paper analyses just two cases as representative of many involving runaway couples – one from the judicial records and the other based upon my field-work in Delhi-Haryana – to argue that legal intervention not only delegitimizes individual attempts to break out of the traditional system of marriage alliances, it also criminalises all such attempts. It highlights the pronounced gender bias against women as her consent is taken cognisance of, without recognising her right to consent or make individual choices. A mutual act is turned unilateral, condemning the woman and holding her responsible to the exclusion of the man, although contradictorily it still punishes him. A man who seeks to divest a guardian of his possession/control of his daughter is termed a rapist and a criminal. The punishment underlines an ideology of guardianship which also means total control of woman and her sexuality, not withstanding her adult status. The judgement delivered in such cases is premised on the view that moral and ethical grounds override questions of the legal and human rights of individuals. In such matters the state acts for and is used by casteist and patriarchal forces, as a primary legitimating institution of popular cultural practices. Standing as an overarching patriarch and acting on behalf of the male guardians of a woman the state criminalises female sexuality, constructing it as essentially transgressive, illegitimate and morally reprehensible. It denies the woman autonomy over her body or the agency to gain control of her life. Instead, it imposes an identity on her that is not her own. This collusion of the family, community and state ends in tragedy.